2017
DOI: 10.1007/s00262-017-2049-0
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic antibodies against cancer stem cells: a promising approach

Abstract: Monoclonal antibodies have been extensively used to treat malignancy along with routine chemotherapeutic drugs. Chemotherapy for metastatic cancer has not been successful in securing long-term remission of disease. This is in part due to the resistance of cancer cells to drugs. One aspect of the drug resistance is the inability of conventional drugs to eliminate cancer stem cells (CSCs) which often constitute less than 1-2% of the whole tumor. In some tumor types, it is possible to identify these cells using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 115 publications
0
7
0
Order By: Relevance
“…Different drugs, such as trastuzumab, lapatinib, and pertuzumab, have been developed in order to interfere with the EGF-HER2 pathway. In particular, trastuzumab is a monoclonal antibody that specifically binds HER2 receptor, and it is the most common drug used in the targeted therapy against HER2-positive breast cancers 5 . Studies with trastuzumab showed as this drug is able to reduce the risk of cancer reoccurrence in early-stage HER2-positive breast cancers, and to improve the overall survival in metastatic late-stage ones 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Different drugs, such as trastuzumab, lapatinib, and pertuzumab, have been developed in order to interfere with the EGF-HER2 pathway. In particular, trastuzumab is a monoclonal antibody that specifically binds HER2 receptor, and it is the most common drug used in the targeted therapy against HER2-positive breast cancers 5 . Studies with trastuzumab showed as this drug is able to reduce the risk of cancer reoccurrence in early-stage HER2-positive breast cancers, and to improve the overall survival in metastatic late-stage ones 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…A another option is to use monoclonal antibodies to target these CSC's. This has already been the subject of several studies [18][19][20]. This new research shows that there is a potential to combine conventional chemotherapy with SB administration for a synergistic and effective treatment that does not produce adverse reactions.…”
Section: Discussionmentioning
confidence: 87%
“…The cancer stem cells in the spheres are highly resistant to death by chemotherapeutic drugs [35,36]. To further validate the role of pS14-WWOX in supporting cancer survival, we measured the extent of cell death in the 4T1 breast cancer stem cell spheres for their uptake of PI, as determined by time-lapse microscopy [28,33,37,38].…”
Section: Resultsmentioning
confidence: 99%